MODEL INTEGRATIF EFEKTIVITAS INTERVENSI BULLYING REMAJA: SYSTEMATIC LITERATURE REVIEW - Oktavia, Thia; Defriyanto, Defriyanto; Murtadho, Ali (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Objective: This study aims to identify, synthesize, and discuss various interventions designed to prevent and address bullying among adolescents, as well as to evaluate their effectiveness, mechanisms of action, and factors influencing successful implementation. Using a Systematic Literature Review (SLR) approach, the study examines relevant scientific publications covering family-based, school-based, peer-led, psychosocial, nursing, media, and physical activity interventions. The findings indicate that multi-level and multi-component approaches involving families, schools, and peers simultaneously are the most effective strategies. Family interventions strengthen positive parenting, school interventions improve the social climate, while psychosocial and physical activity programs support emotional recovery and enhance adolescents’ self-regulation. Successful implementation is supported by stakeholder involvement, facilitator quality, consistent execution, and cultural adaptation, whereas common barriers include limited resources, institutional resistance, and methodological variability. Overall, the study concludes that preventing adolescent bullying requires an integrated, evidence-based, ecologically oriented, and context- sensitive approach, along with further research using stronger designs to reinforce the existing emprical foundation.